2015
DOI: 10.1002/ejoc.201501226
|View full text |Cite
|
Sign up to set email alerts
|

Corannulenecarbaldehyde: High‐­Yielding Synthesis by Rieche Form­ylation and Facile Access to a Variety of Corannulene Derivatives

Abstract: Rieche formylation of corannulene is shown to afford corannulenecarbaldehyde on a multi‐gram scale, in a single step, with an isolated yield of 95 %, and without the need of chromatographic purification. This compound allowed facile access to a wide range of corannulene structures. The developed synthetic routes are expected to facilitate the utility of the corannulene motif – known for its unique structural and electronic properties – in the arena of macromolecular and materials chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…[10,11] During the last decades the chemistry andp hysics of CA-derived buckybowl derivatives was thoroughlys tudied. [12][13][14][15][16][17][18] However,c omparably less work has been carried out in the field of Idpc and its derivatives.T he first synthetic approach towards Idpc by palladium catalyzed cyclization of suitable precursors was reported already in 2000, but lacked generality. [19] The aluminium-oxide mediated cove-regionr ing-closure through CÀF bond activation of fluoroarenes [20] towards pristine Idpc and other bowl-shaped PAHs developed by Amsharov et al in 2012 constituted am ajor breakthrough.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11] During the last decades the chemistry andp hysics of CA-derived buckybowl derivatives was thoroughlys tudied. [12][13][14][15][16][17][18] However,c omparably less work has been carried out in the field of Idpc and its derivatives.T he first synthetic approach towards Idpc by palladium catalyzed cyclization of suitable precursors was reported already in 2000, but lacked generality. [19] The aluminium-oxide mediated cove-regionr ing-closure through CÀF bond activation of fluoroarenes [20] towards pristine Idpc and other bowl-shaped PAHs developed by Amsharov et al in 2012 constituted am ajor breakthrough.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades the chemistry and physics of CA‐derived buckybowl derivatives was thoroughly studied [12–18] . However, comparably less work has been carried out in the field of Idpc and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of corannulene carbaldehyde 102 at a 15 g scale and in an isolated yield of >90% made it possible to explore its application in synthesis of corannulenebased vinylenes 103 through a Wittig olefination reaction with a variety of commercially available phosphonium ylides (Fig. 9a) 61,62 . In subsequent studies, these stilbene-like precursors were shown to undergo a photocyclisation-induced oxidation reaction to yield extended corannulenes 104 62,63 .…”
Section: Photochemistrymentioning
confidence: 99%
“…To a round-bottomed ask cooled to 0 C containing MWCNTs (1.00 g) and dichloromethyl methyl ether (1.5 mL) in anhydrous CH 2 Cl 2 (50 mL), TiCl 4 (1 mL) was added dropwise under N 2 , and the mixture, under the above conditions, was magnetically stirred for 1 h. 42 The stirring was continued at room temperature for 20 h. The product was ltered off. MWCNT-CHO precursor was washed with water (100 mL) and acetone (50 mL) until a colourless ltrate was observed.…”
Section: Rieche Formylation Of Mwcntsmentioning
confidence: 99%